Suprime les parenthèses puis reduire
a= (3x-4)+(-5x-2)
b=3x-(-5+x)+(-3x+3)
c=-4x(aucarre)-(2x(aucare)-3x+1)+2x-3)

2
a=(3x-4)+(-5x-2)
a=-12+10
a=22
merci
developper et réduire si nécessaire
a=3(x+5)
b=2(5x-1)
c=-3a(6-5a)
d=3x+5x(x-2)
e=4a-2(3-5a)
f=3x+5x(4-2x)-2(xaucarre-3x+5)
g=8+2x-2x(3x-a)+5x(3-x)

Réponses

  • Utilisateur Brainly
2013-11-14T20:16:40+01:00
a= (3x-4)+(-5x-2)
=3x-4-5x-2
=-2x-6

b=3x-(-5+x)+(-3x+3)
=3x+5-x-3x+3
=-x+8

c=-4x(aucarre)-(2x(aucare)-3x+1)+2x-3)

=-4x²-(2x²-3x+1)+2x-3
=-4x²-2x²+3x-1+2x-3
=-6x²+5x-4
2013-11-14T20:16:49+01:00
A) (3x-4)+(-5x-2)
   3x-4-5x-2
   -2x-6

b) 3x-(-5+x)+(-3x+3)
   3x+5-x-3x+3
   -x+8
c) -4x²-(2x²-3x+1)+2x-3
   -4x²-2x²+3x-1+2x-3
   -6x²+5x-4